Geometry, morphology, temperature, salinity and density of ice ridges during the transition period from first-year to second-year measured during GoNorth 2023 - Alexandra Pliss; Renée Mie Fredensborg Hansen; Knut Vilhelm Høyland; Christian Katlein; Oskar Gjesdal Veggeland; Nabil Panchi (PANGAEA, 2025)
The GoNorth expedition 2023 was carried out in July - August 2023 in the northern Fram Strait. The geometry, morphology and physical properties of four ridges were investigated during three ice stations by drilling cross-sections with salinity and temperature measurements of the water column and ice-coring. On the first station, one temperature-salinity (TS) core and one density-salinity (DS) core were taken from the ridge together with one salinity (S) core from the level ice. On the second station, two ridges were studied (2.1 and 2.2). Ridge 2.1 had a big void inside of it. Therefore, the TS and DS cores were taken only until the void. The level ice S core was taken regularly. TS and DS cores were taken from ridge 2.2. The same was done at the last station with an additional temperature core from the ridge.